The Many Lives of Equator: History and Analysis of the Late 19th-century Pacific Schooner (Part 1) - Bojakowski, Piotr (The international journal of nautical archaeology, 2025)
In 1888, Matthew Turner, a prolific California shipwright, built Equator for the Wightman Brothers of San Francisco. The ship served as a Pacific merchantman until 1895 during which time it weathered a tropical cyclone that made news around the world and was chartered by Robert Louis Stevenson for his South Pacific adventure. After many conversions, the ship ended up in Puget Sound, Washington, where it was eventually abandoned. In 2023, Equator underwent comprehensive documentation before being commercially dismantled. This article sheds light on Turner’s shipbuilding legacy and details the history and preliminary analysis of Equator as a late 19th-century sailing schooner.